2005
DOI: 10.1111/j.0022-202x.2005.23816.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of a Novel Retroviral-Like Aspartic Protease Specifically Expressed in Human Epidermis

Abstract: Proteases play a pivotal role in epidermal differentiation and desquamation. Separation of a total protein extract from human reconstructed epidermis by two-dimensional gel electrophoresis and subsequent peptide analysis of a specific protein spot identified a new protein exhibiting similarities with the retroviral aspartic protease family. Cloning of the corresponding full-length cDNA revealed an open reading frame encoding for a new protease of 343 amino acids, containing a putative aspartic protease catalyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
83
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(88 citation statements)
references
References 56 publications
5
83
0
Order By: Relevance
“…2). Processing sites of recombinant human SASPase determined from the in vitro autoprocessing product of recombinant protein are also denoted by arrows (13). Note that the processing sites on either side of the protease domain are completely conserved between mouse and human SASPase.…”
Section: Methodsmentioning
confidence: 99%
“…2). Processing sites of recombinant human SASPase determined from the in vitro autoprocessing product of recombinant protein are also denoted by arrows (13). Note that the processing sites on either side of the protease domain are completely conserved between mouse and human SASPase.…”
Section: Methodsmentioning
confidence: 99%
“…The substrate and function of ASPRV1 were previously known only in the context of stratified epithelia (e.g., the stratum corneum of the skin), where it processes profilaggrin and enhances skin hydration (8,9,11,12). We have now found that ASPRV1 is also expressed in the immune system solely by neutrophils and promotes chronic inflammation in EAE.…”
Section: Discussionmentioning
confidence: 76%
“…The results suggest that neutrophils, in EAE, exert macrophage-like functions, as well as a specific effect via the enzyme aspartic peptidase retroviral-like 1 (ASPRV1, also known as SASPase). ASPRV1 is synthesized as a zymogen that contains a putative transmembrane domain and a conserved catalytic domain with a key aspartic acid residue (8)(9)(10). This zymogen can undergo autocleavage under slightly acidic conditions, releasing the catalytic domain that homodimerizes to form an active protease (8,9).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations